Coreopsis sect. Pseudoagarista (Asteraceae: Coreopsideae): molecular phylogeny, chromosome numbers, and comments on taxonomy and distribution. - Crawford, D.J. (2014)
Coreopsis (Asteraceae) sect. Pseudoagarista is the largest section in the genus. It is disjunct between the high mountains of Mexico and high elevations in the Andes. Most species in the section are similar in floral and fruit characters, and aredistinguished primarily by leaf characters. Despite the morphological similarity among all species, the monophyly of the sectionhas been called into question by molecular data. Prior studies of tribe Coreopsideae have been equivocal with, cpDNA markersindicating monophyly but nrDNA ITS sequences have not resolved the section as monophyletic. Expanded cpDNA and nrDNAITS datasets, and statistical (i.e., AU) tests of the ITS and cpDNA topologies provide support that sect. Pseudoagarista is notmonophyletic. Both data partitions strongly support the Mexican and South American subclades as monophyletic. The lowcpDNA sequence variation within each subclade provides no resolution, and thus patterns of evolution within each were examinedusing a phylogenetic framework estimated from ITS data. Sequences from ITS fail to provide high resolution of relationshipsamong South American species, a likely result of a recent, rapid radiation, as is known in other Andean lineages. Divergenceamong species is generally higher in the Mexican species, resulting in better resolution of phylogenetic relationships comparedto South American species. Three ploidy levels (diploid, tetraploid, hexaploid) are known in species from South America, anddiploids and tetraploids have been documented in Mexico. Multiple origins of polyploidy are indicated for both geographic areas.